Srovnávací proteomická analýza krevní plazmy pacientů s mnohočetným myelomem léčených režimy s bortezomibem - Cumová, J; Jedličková, L; Potěšil, D; Sedo, O; Stejskal, K; Potáčová, A; Zdráhal, Z; Hájek, R (Klinicka onkologie, 2012)
BACKGROUNDS: Recently, the term biomarker has become, especially in connection with the term clinical proteomics, one of the most frequent terms in the field of biomedical research. The aim of this work was to select an appropriate pre-fractionation method of blood plasma prior to a subsequent proteomic analysis of low-abundant fraction of proteins by two dimensional gel electrophoresis (2-DE) and mass spectrometry to improve the resolution of 2-DE maps and protein identification. MATERIALS AND METHODS: First, we compared two prefractionation methods (MARS versus ProteoMiner) preceding 2-DE analysis using 10 blood plasma samples. Based on the results of the comparative experiments, low-abundant plasma protein fractions from 18 multiple myeloma patients treated with bortezomib were analyzed. Patients were divided into two groups: a group resistant to chemotherapy (9 patients--disease progression, stable disease) and a group with positive clinical response (9 patients--complete and partial remission). RESULTS AND CONCLUSION: Samples prefractioned by ProteoMiner method yielded 2-DE maps with a significantly increased number of detected protein spots, as compared to immunodepletion method MARS (Multiple Affinity Removal System). Between groups of chemoresistant and sensitive patients treated with bortezomib, 15 differently intense spots were revealed by image analysis. These spots were found to correspond to 10 proteins, as confirmed by mass spectrometry. Seven proteins had significantly lower protein level in the group of chemosensitive patients (serum amyloid P, fibrinogen--gamma chain, retinol-binding protein 4, complement factor C4-A, apolipoprotein E, carboxypeptidase N and complement factor H-related protein 1) and 3 proteins showed significantly higher levels of protein (or were only detected) in the group of chemosensitive patients (serum paraoxonase 1, alpha-1-antitrypsin and complement factor B).
Keywords: senioři; proteomika; Multiple Myeloma; Pyrazines; krevní proteiny; Blood Proteins; kyseliny boronové; Bortezomib; Electrophoresis, Gel, Two-Dimensional; mužské pohlaví; Mass Spectrometry; Antineoplastic Agents; mnohočetný myelom; Proteomics; ženské pohlaví; protinádorové látky; bortezomib; Humans; biologické markery; 2D gelová elektroforéza; Biomarkers; Female; Aged; pyraziny; Boronic Acids; hmotnostní spektrometrie; lidé; Male